Inhibitory effect of Au@Pt-NSs on proliferation, migration, and invasion of EJ bladder carcinoma cells: involvement of cell cycle regulators, signaling pathways, and transcription factor-mediated MMP-9 expression - Shin SS; Noh DH; Hwang B; Lee JW; Park SL; Park SS; Moon B; Kim WJ; Moon SK (International Journal of Nanomedicine, 2018)
Seung-Shick Shin,1,* Dae-Hwa Noh,2,* Byungdoo Hwang,2 Jo-Won Lee,2 Sung Lyea Park,2 Sung-Soo Park,1 Bokyung Moon,2 Wun-Jae Kim,3 Sung-Kwon Moon2 1Department of Food Science and Nutrition, Jeju National University, Jeju, South Korea; 2Department of Food and Nutrition, Chung-Ang University, Anseong, South Korea; 3Department of Urology, Chungbuk National University, Cheongju, Chungbuk, South Korea *These authors contributed equally to this work Background: Although the diverse biological properties of nanoparticles have been studied intensively, research into their mechanism of action is relatively rare. In this study, we investigated the molecular mechanisms of the anticancer activity of heterometallic Au@Pt-nanoseeds (NSs) against bladder cancers.Materials and methods: Mode of action of Au@Pt-NSs was investigated through MTT assay, flow cytometry analysis, Western immunoblots, real-time qPCR, wound-healing migration and invasion assays, zymography, and electrophoretic mobility shift assay (EMSA).Results: Treatment with Au@Pt-NSs significantly inhibited the proliferation of EJ cells in a dose-dependent manner by inducing G1 phase cell cycle arrest. Among the regulators associated with the G1 cell cycle phase, CDK2, CDK4, cyclin D1, cyclin E, and p21WAF1 were shown to participate in the inhibitory pathways of Au@Pt-NSs. In addition, treatment with Au@Pt-NSs led to upregulation of phospho-p38 MAPK and downregulation of phospho-AKT in EJ cells. Interestingly, Au@Pt-NSs inhibited the migratory and invasive potential of the cells, which was attributed to the suppression of the enzymatic activity of matrix metalloproteinase-9 (MMP-9). Using MMP-9-specific oligonucleotides, we showed that transcription factors such as NF-κB and Sp-1 were responsible for the MMP-9-mediated metastatic potential of EJ cells.Conclusion: Au@Pt-NSs significantly limited the progression, migration, and invasion of bladder cancer EJ cells. Our data represent a novel insight into developing cisplatin-like chemotherapeutic reagents with fewer side effects and provide useful information on molecular markers to monitor patients under Au@Pt-NSs-based chemotherapy. Keywords: nanoseeds, nanomedicine, bladder cancer, molecular mechanism